Pengaruh Variasi Kecepatan Aliran Udara Primer dan Penambahan Udara Pada Reaktor Kompor Gasifikasi Sekam Padi Metode Top-Lit Up Draft Dengan Perbedaan Diameter Silinder Reaktor - Wiguna, Rifki Arya; , Wijianto, ST, M.Eng.Sc (2017)
One of the utilization of biomass energy to reduce air emissions is to use gasification stove TLUD method. The addition amount of air and the difference in the diameter on the reactor is one of the improvisation of cook stoves gasification TLUD methods design used on the stove in this study. The purpose of this study was to describe the temperature of the flame, time flame effective, and calculate the thermal efficiency of the gasification stove TLUD methods with the differences of the diameter of inner cylinder of the reactor. Testing is done by taking data of the temperature of flame and temperature of boiling water every 30 seconds in the variation of the flow rate of primary air (8 m/s, 10 m/s, 12 m/s) without the addition of air and with the addition of air 2.5 m/s on the reactors wall of gasification cook stoves TLUD method. Total operating time is recorded on each test. The results of this study showed that the highest average temperature is at 10 m/s. The higher the speed of primary air flow the less time flame effective is produced. Thermal efficiency is best obtained on testing variations of the primary air flow velocity of 10 m / s with the addition of air 2.5 m / s at the reactor wall.